Negotiating the Meaning of Marriage Registration in Indonesia’s Digital Space: A Challenge for Legal Literacy Management in Education - Sifa Mulya Nurani; Triana Apriyanita; Rezki Baskoro (Al-Qalam Institue, 2026)
The rise of online secret marriage services in Indonesia presents a new dynamic that challenges conventional understandings of unregistered marriage by turning it into a digitized and commodified service. This study analyzes public discourse on these services and develops strategies to raise awareness about the risks of secret marriages and the importance of registration, particularly from the perspectives of educational management and legal literacy. Using a qualitative approach, content and thematic analyses were applied to 205 netizen comments from three YouTube videos. Findings show public responses revolve around three interrelated dimensions: religious orientation, administrative considerations, and family protection concerns, reflecting tensions between religious legitimacy, perceptions of state service rationality, and the need for legal and social protection. COM-B framework analysis indicates that attitudes toward marriage registration are influenced by normative understanding, experiences with administrative procedures, and value-driven motivations. The study suggests that addressing unregistered marriages in the digital era requires multilevel interventions, including strengthening legal and digital literacy, integrating marriage law awareness into curricula, improving registration services, and governing digital spaces. This research contributes by linking digitized secret marriage phenomena with educational management strategies to shape public understanding, behavior, and social protection.